RNA-Binding Proteins: The Key Modulator in Stress Granule Formation and Abiotic Stress Response - Yan, Yanyan; Gan, Jianghuang; Tao, Yilin; Okita, Thomas W.; Tian, Li (Frontiers in Plant Science, 2022)
To cope with abiotic environmental stress, plants rapidly change their gene expression transcriptionally and post-transcriptionally, the latter by translational suppression of selected proteins and the assembly of cytoplasmic stress granules (SGs) that sequester mRNA transcripts. RNA-binding proteins (RBPs) are the major players in these post-transcriptional processes, which control RNA processing in the nucleus, their export from the nucleus, and overall RNA metabolism in the cytoplasm. Because of their diverse modular domain structures, various RBP types dynamically co-assemble with their targeted RNAs and interacting proteins to form SGs, a process that finely regulates stress-responsive gene expression. This review summarizes recent findings on the involvement of RBPs in adapting plants to various abiotic stresses via modulation of specific gene expression events and SG formation. The relationship of these processes with the stress hormone abscisic acid (ABA) is discussed.